Study Literatur: Hasil Belajar pada Penggunaan Media Pembelajaran Komik Matematika - Maulidia, Nabillah; Andika Setyo Budi Lestari (Ar-Riyadhiyyat: Journal of Mathematics Education, 2024)
This research aims to assess learning outcomes through the utilization of mathematical comic media using the Systematic Literature Review (SLR) method. The data collection process involves the application of Publish or Perish, referencing Google Scholar and Garuda – Garba Rujukan Digital, selecting 20 articles out of a total of 100 that meet the criteria of compatibility and relevance. The publication year range spans from 2018 to 2023 to ensure accuracy and data relevance. From the literature analysis, the researcher compiles several key points. The use of comics in mathematics learning can enhance learning outcomes by leveraging mathematical visualization to help students understand concepts more effectively. Furthermore, the use of comics makes mathematics learning more engaging and enjoyable. The ability of comics to illustrate abstract mathematical concepts also facilitates student comprehension. The level of completeness of learning outcomes has shown a significant improvement in various studies, reaching an excellent category and exceeding the Minimum Mastery Criteria (KKM). Findings from various sources indicate that mathematical comics can be considered an innovative and effective strategy in improving students' learning outcomes, particularly in understanding challenging mathematical concepts.